Effects of tailoring and dehydrated cross-linking on morphology evolution of ordered mesoporous carbons. Issue 23 (17th February 2016) - Zhang, Jiaxi; Liu, Dandan; Song, Huiyu; Liang, Zhenxing; Guo, Xuefeng; Du, Li; Liao, Shijun
Abstract : Self-templated in situ construction of organic mesoporous carbon materials through tailoring of micelles and by dehydrated cross-linking effects. Abstract : In this study, using a template (Pluronic P123) as an in situ carbon source, ordered mesoporous carbons (OMC) were successfully synthesized through directing carbonization of templates. Two key factors in the morphology evolution of mesoporous carbon materials were introduced, one is the tailoring role of micelles by ethanediol, and the other is the dehydrated cross-linking effect by sulfuric acid. Through the two factors, the morphology of as-synthesized ordered mesoporous carbons can be altered from bulks to rods and even to sheets. Transmission electron microscopy (TEM) showed ordered mesoporous carbon rods (OMCR) and ordered mesoporous carbons sheets (OMCS) possessed regular morphology and good mesopore structure. Nitrogen adsorption–desorption analysis confirmed that both OMCR and OMCS had high surface area and uniform mesopore distribution, OMCR had the highest surface area (919 m 2 g −1 ) and OMCS had the biggest pore size (9.11 nm). This study also showed that OMCR and OMCS were good carbon carriers; the size of Pt loading nanoparticles can be decreased to 3 nm and Pt/OMCS especially presents very high Pt dispersion and uniformly smallest Pt nanoparticles (2.49 nm).